(untitled) (Journal of Geography and Environmental Management, 2019)
Over a long period of economic activities on the territory of Central Asia have accumulated millions of tons of industrial and municipal solid wastes. As a result, there is a violation of ecosystems, a decrease in biodiversity, pollution and land degradation in large areas, leading to serious socio-economic consequences. Many social and economic problems of this region lies a historically developed imbalance as the countries consume resources out of a proportion with their manufacture. The purpose of this research was the study and analysis of environmental pollution in Central Asia. The main direction of the study is the assessment of solid waste pollution of production and consumption and the development of ways to solve the problem in this region. In order to the radically change of the current situation and the status of activities for environmental protection and sustainable development, it is necessary to introduce the principles of a green economy implemented at the national and regional levels. The introduction of the principles of sustainable development is a great importance in solving this problem. At present, the Central Asian countries are moving towards the practical implementation of the principles of sustainable development in strategic documents and practices of public waste management. The issue of waste management, taking into account their transboundary effect, and the environment as a whole is possible only on the principles of cooperation. In order to ensure timely solution to this problem is necessary to improve and harmonize the scheme of waste management at the state level and through regional cooperation. Growing global threats related to climate change, energy, water and food security problems, as well as regional conflicts require new solutions and integration of the efforts of the entire community of this region. To ensure timely solution of this problem, it is necessary to improve and harmonize the waste management scheme at the state level and through regional cooperation. The article summarizes the problems, directions of further integration in the field of waste management.